Development of an electric measurement system for rapid determination of the friction coefficient - Rónai, László (Design of Machines and Structures, 2020)
Development of an electric measurement system for rapid determination of the friction coefficient is discussed in this paper. The electric system is capable to use with a ball cage guide bush unit. Two beam load cells are included into the system and the measured values of the forces are processed by microcontrollers. In the course of measurements, normal- and tangential forces of inner or outer surfaces of different enamelled specimens could be determined. A data acquisition program is developed to record the force values to a personal computer. Linear interpolation method is required to synchronize the values of the load cells, which is necessary to calculate the coefficient of friction.